The Worker’s Right to Refrain from Fulfilling The Obligation to Work Due to The Non-Provision of Occupational Health and Safety Services Under Turkish Law - Akkoyun, Deniz Bade (Border Crossing, 2024)
The right to life of individuals is guaranteed by the Turkish Constitution and various international treaties concerning human rights. In the event of a serious and imminent hazard in the workplace, workers’ refrainment from working is a manifestation of the most basic human right, the right to life. In such hazardous situations, workers cannot be expected to continue their work and their rights cannot be restricted due to their refrainment. In other words, it is a requirement of the modern social state to ensure that the workers, whose rights are guaranteed within the framework of the relevant legislation, acquire their wages and other rights during this period. The Turkish Occupational Health and Safety Law regulates the scope and conditions of this right. Should the employer not comply with their obligation to take the necessary measures to eliminate hazardous situations within a reasonable amount of time after learning, the worker may then be entitled to the right to termination.